Impact of Transverse Reinforcement Ratio on Flexural Behaviour of Self Compact High Strength Concrete (SCHSC) Beams - Mohamad Isa Zohri, Meor Abdul Azziim (Universiti Teknologi PETRONAS, 2018)
This research focuses on the study of the influence of transverse reinforcement ratio on failure behaviour of Self Compact High Strength Concrete (SCHSC) with and without steel fibres. In this study, the mechanical properties of the SCHSC is been tested in term of compressive, tensile and flexural strength with selected mix design that acquire 3% of steel fibres and to compare with non-steel fibres SCHS Concrete. The cementitious composite used in this research is composed by Ordinary Portland Cement (OPC), silica fume, fly ash, river sand, quartz sand, superplasticizer, water and steel fibres. The average result of SCHSC sampling on mechanical properties for compressive test is 91.24 Mpa compared with adding steel fibres is 101.25 Mpa.